Development of reprogenetics and its demographic aspects - Devedžić Mirjana M. (Stanovništvo, 2004)
The development of reprogenetics during the last two decades of the XX century has brought a new age of reproduction. The paper surveys different types of reprogenetics in a wider sense, i.e. different assisted reproductive technologies (ART) that include manipulation of female reproductive cell out of a woman's womb. Development of reprogenetics is documented by available quantitative indicators of the number and success of ART procedures in developed countries at the beginning of the XXI century. Since 1978, when the first baby was born from in vitro fertilization, the number of children born that way has reached 1% of all children, and in some countries even over 3%. Moreover, existing documentation is incomplete and does not include all forms of assisted reproduction - in reality, the importance of assisted reproduction is even higher and becomes demographically significant. Hence the paper indicates existing and potential effects of the ART development on the demographic development i.e. on specific demographic aspects of this phenomenon. It also points out the effects on the level of fertility, on the changes of direct fertility determinants, and on the levels of mortality and infant mortality, as well as a new understanding of birth control, the possibility of affecting biological structures, and the changes of the fundaments of marriage and family. Development perspectives of reprogenetics are also being raised in the context of bioethical discussions and indicate ethical dilemmas related to assisted reproduction. Solutions to the dilemmas define the scope of applying new reproductive technologies in the future.